Amazon Peasant Societies in a Changing Environment - Adams, C. (Springer, 2017)
Amazonia is never quite what it seems. Despite regular attention in the media and numerous academic studies the Brazilian Amazon is rarely appreciated as a historical place home to a range of different societies. Often left invisible are the families who are making a living from the rivers and forests of the region. Broadly characterizing these people as peasants Amazon Peasant Societies in a Changing Environment seeks to bring together research by anthropologists, historians, political ecologists and biologists.